"Not Anybody can be a Dad": The Intergenerational Transmission of Masculinity Among Incarcerated Men. (September 2022) - Umamaheswar, Janani; Tadros, Eman
Despite an important and burgeoning literature correcting oversimplified portrayals of incarcerated men as "hypermasculine" and aggressive, research on men's prison masculinities has not yet been sufficiently incorporated into prison treatment and therapy programs. In this article, we draw on in-depth interviews with 28 incarcerated men to explore the intergenerational transmission of masculinity in the family setting, highlighting how incarcerated men adapt, modify, and/or challenge the masculinity scripts they inherited from their fathers (or father figures) when reflecting on their own attitudes toward fatherhood. We use these insights to advocate for gender-responsive feminist family therapy that incorporates incarcerated men's constructions of masculinity in efforts to restore and strengthen these men's familial ties.